Proteínas do látex de Calotropis procera (Ait.)R.Br. e seus efeitos sobre pragas agrícolas. - Freitas, Cleverson Diniz Teixeira de (2006)
The plant Calotropis procera belonging to Asclepiadaceae is found around a vast extension of the Northeast from Brazil. It is a lactifers plant and its endogenous production of latex is admirable. Despite continuous reports appearing in the literature give mention to the medicinal properties of different parts of the plant, including the latex, there is not scientific approaches comprising biochemical of functional aspects of the latex from C. procera. The aims this work was determine the presence of endogenous enzymatic activities and inhibitory activity against different proteases and a-amylase, to evaluate insecticidal properties against different crop pests and to correlate enzymatic content and insecticidal action with possible role of the latex in protecting the plant to insect pathogens. The major soluble protein fraction from the latex was prepared following the protocol previously defined that includes centrifugations and dialysis steps. The protein fraction devoided of rubber and low molecular mass molecules was assayed to the presence of endogenous proteolytic activities as well as a-amylase activity. Even, the presence of inhibitor of such activities was investigated. Additionally the latex proteins were submitted to proteolysis by digestive content of different insects. Bioassays base on artificial diets with different contents of native, pronase digested or heated treated (98 °C) latex proteins were performed against six insects belonging to 4 different orders. Increment in bodyweight of larvae, time of development and percentage of survive were the parameters considered to analyze detrimental effects of latex proteins upon insects. The effect of latex proteins upon Callosbruchus maculatus insects by continuous exposure until F-6 generation was reached was performed. It was found strong endogenous proteolytic activity and latex proteins were resistent to proteolysis by insect digestive extracts. In addition chitinolytic activity was also detected. The latex exhibited insecticidal activity against different insect groups and this effect may be correlated to the presence of a cysteine protease inhibitor associated to its proteolytic properties and chitinolytic activity. It is suggested that the protein fraction of the latex from Calotropis procera plays a relevant role in defending the plant against pathogens.